Effects of repetitive transcranial magnetic stimulation combined with repetitive peripheral magnetic stimulation on upper limb motor function after stroke: a systematic review and meta-analysis - Luo, Shanshan; Wen, Zhu; Liu, Ying; Sun, Tao; Xu, Li; Yu, Qian (Frontiers in Neurology, 2024)
ObjectiveTo evaluate the effectiveness of repetitive transcranial magnetic stimulation (rTMS) combined with repetitive peripheral magnetic stimulation (rPMS) on upper limb motor dysfunction after stroke.MethodsWe systematically searched databases up to May 2024, including PubMed, Embase, Cochrane Library, Web of Science, CNKI, VIP, Wanfang, and CBM. Randomized controlled trials (RCTs) examining the application of rTMS combined rPMS on upper limb motor dysfunction after stroke were included based on predefined inclusion criteria. We used Cochrane Risk of Bias 2 tool to assess bias risk of the included RCTs. Meta-analysis was conducted using RevMan 5.4 and Stata 17.0 software.ResultsA total of 9 RCTs involving 483 participants were included in this study. Compared with the control groups that used either conventional therapy or rTMS alone, the experimental group that used rTMS combined rPMS showed significant improvements in stroke patients' upper limb motor function [MD = 3.65, 95% CI (2.75, 4.54), P < 0.05], ability of daily living [MD = 4.50, 95% CI (3.50, 5.50), P < 0.05], and spasticity [MD = –0.34, 95% CI (−0.48, −0.20), P < 0.05]. Meanwhile, in terms of neurophysiological indicators, significant differences were found both for motor evoked potential latency [MD = −1.77, 95% CI (−3.19, −0.35), P < 0.05] and motor evoked potential amplitude [MD = 0.25, 95% CI (0.01, 0.49), P < 0.05].ConclusionThis study provides low-level evidence that the therapy of LF-rTMS or HF-rTMS combined with rPMS can improve the upper limb motor function and daily living ability of stroke patients. However, given that the low quality of the evidence for the evaluation results, further evidence from high-quality studies is needed to substantiate this conclusion.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024539195, PROSPERO Platform [CRD42024539195].